Faktor-faktor yang Mempengaruhi Kepatuhan Pengobatan Tuberkulosis: A Systematic Review - Vivi Meiti Berhimpong; Tintin Sukartini (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Background: The biggest problem of transmission of infectious diseases to date was disobedience in undergoing treatment which makes patients resistant to drugs and threatens other public health by increasing morbidity and mortality (mortality). Objective: To identify factors that influence the leveled of patient compliance with tuberculosis treatment. Methods: This systematic review was based on preferred reporting items for systematic reviews and meta-analyses (PRISMA). The database used in this studied was Scopus, ProQuest and PubMed were limited to the last 5 years of publication from 2016 to 2020, full-text article and in English. The keywords used were "tuberculosis" and "adherence" and "DOT TB treatment. This systematic review uses 10 articles that fit the inclusion criteria outcome. Results: Factors influencing the relationship were family support, peered groups, ties, sufficient economics, knowledge, recognition, and early signs, self-awareness for treatment, motivation, self-efficacy owned by a social strengthening of the government or institution, health education from Healthcare workers (HCWs). Conclusion: various factors that influence medication adherence were considered necessary to be addressed jointly from all levels of work procedures. However, careful preparation was needed, especially self-acceptance and education to received new knowledge and understanding. Keywords: tuberculosis; adherence; DOT TB treatment ABSTRAK Latar belakang: Masalah terbesar penularan penyakit infeksi menular hingga saat ini adalah ketidakpatuhan menjalani pengobatan sehingga menjadikan pasien menjadi resisten terhadap obat dan mengancam kesehatan masyarakat lainnya dengan peningkatan kesakitan (morbiditas) serta kematian (mortalitas). Tujuan: untuk mengidentifikasi faktor-faktor yang mempengaruhi tingkat kepatuhan pasien terhadap pengobatan tuberkulosis. Metode: Systematic Review ini disusun berdasarkan Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA). Database yang digunakan dalam penelitian ini adalah Scopus, Proquest dan Pubmed terbatas untuk publikasi 5 tahun terakhir dari 2016 hingga 2020, full text article dan berbahasa Inggris. Kata kunci yang digunakan adalah “tuberculosis” AND “adherence” AND “DOT TB treatment. Systematic review ini menggunakan 10 artikel yang sesuai dengan kriteria inklusi Hasil: Faktor yang mempengaruhi kepatuhan adalah dukungan keluarga, kelompok sebaya, etnis, ekonomi yang cukup, pengetahuan, pengenalan terdapat tanda dan gejala awal, kesadaran diri untuk berobat, motivasi, self-efficacy adanya jaminan sosial dari pemerintah atau lembaga, pendidikan kesehatan dari petugas kesehatan. Kesimpulan: Berbagai faktor yang mempengaruhi kepatuhan pengobatan dipandang perlu untuk diatasi bersama dari semua lapisan tata kerja. Namun, perlu persiapan matang terutama penerimaan diri serta edukasi untuk untuk menerima pengetahuan dan pemahaman baru. Kata kunci: tuberkulosis; kepatuhan; DOT TB treatment